Synthesis and evaluation of pyridine-derived bedaquiline analogues containing modifications at the A-ring subunit - Barbaro, Lisa (RSC Med Chem, 2021)
Despite promising efficacy, the clinical use of the anti-tubercular therapeutic bedaquiline has been restricted due to safety concerns. To date, limited SAR studies have focused on the quinoline ring (A-ring), and as such, we set out to explore modifications within this region in an attempt to discover new bedaquiline variants with an improved safety profile. We herein report the development of unique synthetic strategies that facilitated access to novel bedaquiline analogues leading to the discovery that anti-tubercular activity could be retained following replacement of the quinoline motif with pyridine heterocycles. This discovery is anticipated to open up multiple new avenues for exploration in the design of improved anti-tubercular therapeutics.